Interception and use of solar radiation by maize, as modifying soil tillage, row spacing and irrigation water availability - Kunz, Jefferson Horn; Bergonci, João Ito; Bergamaschi, Homero; Dalmago, Genei Antonio; Heckler, Bruna Maria Machado; Comiran, Flavia (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the efficiency of interception and use of photosynthetically active radiation (PAR) by maize crops submitted to different conditions of soil tillage, plant arrangement, and water availability. Maize was cropped in no-tillage and conventional tillage, combined to treatments of soil water availability (irrigated and in rain fed), and plant row spacing (40 and 80 cm among rows). Sensors were installed in each treatment, for measuring the PAR transmitted by the canopy to the soil surface, while the incoming PAR was measured above the crop. Increments of efficiency of interception were obtained by reducing the row spacing in all treatments. Higher values of efficiency of interception were observed in no-tillage than in conventional tillage. Water deficits reduced efficiency of interception due to the rolling up of leaves, and this effect was higher in conventional tillage than in no-tillage, for both row spacings. Although the highest efficiency of interception was obtained with 0.4 m spacing, the efficiency of PAR use did not differ among treatments of row spacing. However, efficiency of use of maize crops was reduced by water deficits.